Research on Machine Learning with Algorithms and Development - Yu, Liqiang; Zhao, Xinyu; Huang, Jiaxin; Hu, Hao; Liu, Bo (Journal of Theory and Practice of Engineering Science, 2023)
Machine Learning, as one of the key technologies in the field of artificial intelligence, has made significant advancements in recent years. This study provides a relatively systematic introduction to machine learning. Firstly, it gives an overview of the historical development of machine learning, and then focuses on the analysis of classical algorithms in machine learning. Subsequently, it elucidates the latest research advancements in machine learning, aiming to comprehensively explore the applications of machine learning in various domains and discuss potential future directions.